Analysis and evaluation of nutritional components in liver of large yellow croaker (Pseudosciaena crocea). Issue 1 (1st January 2020) - Dou, Xin; Wang, Yue Qi; Wu, Yan Yan; Hu, Xiao; Yang, Shao Ling; Li, Chun Sheng; Cen, Jian Wei
ABSTRACT: During the processing of the large yellow croaker, the further utilization of the by-products (e.g., the liver) generated in the processing process can provide opportunities for value addition and increase profitability, promoting the sustainable use of raw materials. Therefore, we have studied the detailed nutritional composition of the large yellow croaker liver (LYCL), which ultimately helps in the development of nutritional and functional products. The results showed that the LYCL has a lower moisture content (45.71%) than fish meat, 8.25% protein, and 37.97% fats. In addition, LYCL contained the full range of amino acids. Unsaturated fatty acids accounted for 62.63%, of which EPA and DHA account for 9.42%. It was rich in phospholipids, vitamins and trace elements. Heavy metal elements such as Hg, As, Cd were lower than the heavy metal limit standards for fish in China. Aldehydes, ketones and alcohols in the liver have the greatest impact on odor.